DESIGN AND IMPLEMENTATION OF AN ONLINE TEACHING AND LEARNING MANAGEMENT SYSTEM - Adedoyin, Adeyinka; Enebe, F. O.; Oyekunle, R. A.; Balogun, N. A. (FUDMA Journal of Sciences, 2023)
The global education system was impacted by the coronavirus pandemic. To stop the coronavirus from spreading, all schools, colleges, and universities were closed. Students, instructors, and parents all experienced challenges while schools were closed. So, distance learning was a solution to continue the education system. Unfortunately, in a developing country, it was challenging to adopt distance learning due lack of network infrastructures, computers, epileptic power supply, and good internet access. In order to circumvent some of these challenges different online platforms were employed. However, they came with some limitations, for example, the freemium subscription scheme, which allows users to use basic features of the system but requires a certain amount on a predefined basis to access extra needed features. In addition, to use video conferencing in some of the existing LMS you are required to leave the app for another app, for example, to use video conferencing in google classroom you are required to use google meetings. This study aims to create an online E-Learning System that provides all in one tool for teachers to develop and administer courses online. The LMS comes with various functions such as creating learning plans, implementing learning processes, and assessing or evaluating learning processes. Our LMS presents instruction through content creation and storage, sees student participation, and assesses student performance online. The Online Learning System was designed using JavaScript (Vue), PHP (server-side programming Language), and NoSQL as the database. The developed system was evaluated by potential users and found to meet predefined user requirements.
Keywords: Learning management system; e-learning; open; distance learning